(untitled) (Journal of the Bangladesh Agricultural University, 2010)
An experiment was undertaken to determine the conception rate of native sheep by using Artificial Insemination with liquid ram semen. The semen was collected from ram using artificial vagina and the was stored in a refrigerator (4°C) for three days. The volume of semen was extended with egg yolk citrate diluter. A total of 63 ewes were inseminated with stored liquid semen collected from 15 rams by AV method. The total number of spermatozoa, live-dead, normal-abnormal, sperm motility and the pH was observed regularly. The average semen volume per ejaculate was 0.76-1.00ml and the sperm concentration was 2.37x109 - 4.30x109 per ejaculate. The number of normal spermatozoa and the pH was almost similar irrespective of days of storage. Number of live spermatozoa and the sperm motility were reduced with the increasing age of semen. The average conception rate (%) was obtained as 63.61, 61.90, 52.38 and 47.61 with sperm in zero, 1st, 2nd and 3rd day storage respectively. Keywords: Preservation; Liquid semen; Quality; Artificial insemination; Sheep DOI: 10.3329/jbau.v7i2.4739 J. Bangladesh Agril. Univ. 7(2): 305-308, 2009